(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we study a host-parasitoid model with Holling II Functional response, where we focus on a special case: the carrying capacity K_2 for parasitoids is equal to a critical value r_1η. It is shown that the model can undergo Bogdanov-Takens bifurcation. The approximate expressions for saddle-node, Homoclinic and Hopf bifurcation curves are calculated. Numerical simulations, including bifurcation diagrams and corresponding phase portraits, are also given to illustrate the theoretical results.